2013
DOI: 10.1016/j.bpj.2013.04.035
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Na+/K+ Selectivity in Mammalian Voltage-Gated Sodium Channels Based on Molecular Dynamics Simulation

Abstract: Voltage-gated sodium (Nav) channels and their Na⁺/K⁺ selectivity are of great importance in the mammalian neuronal signaling. According to mutational analysis, the Na⁺/K⁺ selectivity in mammalian Nav channels is mainly determined by the Lys and Asp/Glu residues located at the constriction site within the selectivity filter. Despite successful molecular dynamics simulations conducted on the prokaryotic Nav channels, the lack of Lys at the constriction site of prokaryotic Nav channels limits how much can be lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 54 publications
11
53
1
Order By: Relevance
“…As expected, the WT and DEAA mutant allow both Na + and K + ions to quickly permeate into the SF (Fig B in S1 File), consistent with the weak Na + /K + selectivity of these channels reported in our previous works [28, 45]. …”
Section: Resultssupporting
confidence: 91%
“…As expected, the WT and DEAA mutant allow both Na + and K + ions to quickly permeate into the SF (Fig B in S1 File), consistent with the weak Na + /K + selectivity of these channels reported in our previous works [28, 45]. …”
Section: Resultssupporting
confidence: 91%
“… 52 , 53 Each of these two SFs plays a distinct role in facilitating ion permeation. 54 , 55 The outer SF (EEDD ring) encompasses four amino acid residues, namely E375 (DI), E901 (DII), D1423 (DIII), and D1714 (DIV). These residues ( Figure 1D ) are spread across the four domains.…”
Section: Resultsmentioning
confidence: 99%
“… 63 Furthermore, Xia et al reported that the long side chain of the K residue of VGSC adopts a few distinct conformational states, from which only specific states can allow the passage of sodium. 54 These states were grouped into two main categories; the “on-states” where sodium is allowed to permeate and the “off-states” where the pore is blocked by the side chain of K residues. Xia, moreover, showed that, in the “off-states”, the side chain of K1419 interacts with the facing carboxylate group of E898 from the DEKA filter and the backbone/side chain oxygens of S1710 – one of the pore lining residues.…”
Section: Resultsmentioning
confidence: 99%
“…The resolution of the first such structure (3.5 Å), however, was too low to determine the details of the sites of the ions in the SF, whilst the latter structures contained channel blocker ligands which interfered with ion binding. The sodium ion binding site locations and mechanisms for ion selectivity have also been predicted by a number of molecular dynamics (MD) studies, although they differ considerably in their details (Amaral et al , 2012; Chakrabarti et al , 2013; Stock et al , 2013; Ulmschneider et al , 2013; Xia et al , 2013; Zhang et al , 2013; Boiteux et al , 2014; Furini et al , 2014). …”
Section: Introductionmentioning
confidence: 99%